2017
DOI: 10.1521/jscp.2017.36.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Social Surrogate Use in Those Exposed to Trauma: I Get By with a Little Help from My (Fictional) Friends

Abstract: Traumatic events bring an increased need for social connection but paradoxically can make relationships more difficult. The current research examines the unique role social surrogates such as favorite TV shows, books, and celebrities may play in fulfilling the social needs of people who have experienced trauma. Across two studies we predicted and found that experiencing traumatic events is associated with higher interest in using social surrogates. Furthermore, individuals who have experienced trauma without d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…As a trait, some residents may not favor the use of problem solving as a coping strategy, which could have contributed to greater traumatic stress when faced with unprecedented events such as the pandemic. As a state, residents currently experiencing traumatic stress may also rely less on problem solving as a coping strategy, preferring alternatives such as seeking social support, as found in this study [ 19 ]. This could also be a function of the nature of the stressor, as situations that are appraised as being solvable are more likely to induce problem-focused coping, while situations that are appraised as being unchangeable are more likely to induce emotion-focused coping [ 20 ].…”
Section: Discussionmentioning
confidence: 92%
“…As a trait, some residents may not favor the use of problem solving as a coping strategy, which could have contributed to greater traumatic stress when faced with unprecedented events such as the pandemic. As a state, residents currently experiencing traumatic stress may also rely less on problem solving as a coping strategy, preferring alternatives such as seeking social support, as found in this study [ 19 ]. This could also be a function of the nature of the stressor, as situations that are appraised as being solvable are more likely to induce problem-focused coping, while situations that are appraised as being unchangeable are more likely to induce emotion-focused coping [ 20 ].…”
Section: Discussionmentioning
confidence: 92%
“…For instance, for those who had social challenges such as factors related to cognition (McCutcheon et al 2003 ), anxiety (Cole and Leets 1999 ; Green and Brock 1998 ; Papachrissi and Rubin 2000 ), introversion (Weaver 2003 ), fear of rejection (Derrick et al 2019 ), loneliness (Greenwood and Long 2009 ), or self-esteem (Derrick et al 2008 ), engaging in parasocial behaviors significantly aided some measures of well-being. Another study found PSI helpful for those who had experienced trauma, but not for those post traumatic with stress disorder (Gabriel et al 2017 ). Even anecdotally, the evidence for parasocial processes aiding well-being seems to be everywhere.…”
Section: Outcomes Of Parasocial Interaction On Individuals and Groupsmentioning
confidence: 99%
“…The social support deterioration model (Barrera, 1986) suggests that stress erodes one's perception of the availability or effectiveness of social support, which leads to persistent difficulties in forming and maintaining social relationships (Hawkley & Cacioppo, 2010;Seeds, Harkness, & Quilty, 2010). However, the need for these relationships is increased among people with these impairments (Gabriel, Read, Young, Bachrach, & Troisi, 2017). The vulnerability-stress model and the stress-sensitisation model suggest that childhood adversity may cause heightened sensitivity to subsequent stressors, which in turn may trigger psychological distress (Danese & McEwen, 2012;Heim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%